MARKETING ASSESSMENT OF DRUGS USED FOR TREATMENT OF ACID-RELATED DISEASES IN BISHKEK - E.B. MURZABAEVA; I.Z. ISMAILOV (Avicenna Tajik State Medical University, 2020)
Objective: Marketing assessment of anti-ulcer medicines in pharmacies in Bishkek. Methods: The study was used by data from the Department of Medicines and Medical Technology at the Ministry of Health of the Kyrgyz Republic on the registration of pharmaceutical products in the KR - State Registry of Medicines and Medical Products of 2019, as well as price sheets and invoices of wholesale pharmaceutical companies and retail pharmacies in Bishkek. Results: Depending on the value of the turnover rate (TR), the drugs were divided into three groups: drugs with slow TR (0.5 < К < 1.0); drugs with constant TR (0.26 < К < 0.49); drugs with high TR (0 < К < 0.25). According to the results of studies, proton pump inhibitors and colloidal bismuth-based drugs are high-end drugs of TR. Conclusion: We have determined that the pharmaceutical market in Bishkek demonstrates incomplete saturation of anti-ulcer drugs from the total number of registered medicines. At the same time, the largest part of the range are drugs from the group of proton pump inhibitors.